Financial support failure and health results: The Peruvian case - Jorge Guillen (PLoS ONE, 2023)
The paper shed the light in analyzing the efficiency of Peruvian Government Financial Support in comparison with some countries in the Latin American Region and worldwide. The Covid 19 Pandemic enforced governments to apply the “Hammer Blow” which affected negatively the economy producing recession and unemployment. Governments offset the latter effect by applying subsidy policies to the Poor and then reduce the negative economic consequences of the general lockdown without getting COVID. Our study performs a Difference and Difference Model (DID) to evaluate the effectiveness of the latter policy.